EVALUASI KINERJA SIMPANG TAK BERSINYAL ANTARA JALAN SULTAN HAMENGKUBUWONO 9 DAN JALAN CAKUNG CILINCING RAYA - utama, dwinanta (Jurnal Sains dan Teknologi Indonesia, 2006)
Unsignalize intersection is very effective because it has less average delay compare to signalize intersection. But when the traffic volume getting higher the capacity of unsignalize intersection may not be able to maintain a proper intersection performance. Several alternatives improvement should be analyzed to overcome the unsignalize intersection problem. If the improvement alternatives fail then the unsignalize intersection should be changed as a signalize one. This condition will be implemented at 4 legs intersection between jalan Sultan Hamengkubuwono 9 and Jalan Cakung Cilincing Raya. Kaji software was implemented to do this intersection evaluation.